Antioxidant Activity as an Indicator of the Efficiency of Plant Extract-Mediated Synthesis of Zinc Oxide Nanoparticles - Joelis Vera; Wence Herrera; Edward Hermosilla; Marcela Díaz; Javiera Parada; Amedea B. Seabra; Gonzalo Tortella; Héctor Pesenti; Gustavo Ciudad; Olga Rubilar (MDPI AG, 2023)
The green synthesis of zinc oxide nanoparticles (ZnO NPs) using a diverse range of plant species has been extensively reported. Despite the success achieved by biogenic synthesis, there are problems with the control and prediction of the properties of ZnO NPs, due to phytochemical diversity between plant species. In this sense, the main objective of our work was to investigate the effect of the antioxidant activity (AA) of plant extracts on the physicochemical characteristics of ZnO NPs (production yield, chemical composition, polydispersity index (PDI), surface charge (ζ-potential) and average particle size). In order to accomplish this objective, four plant extract with different antioxidant activities were used: Galega officinalis, Buddleja globosa, Eucalyptus globulus, and Aristotelia chilensis. Phytochemical screening, quantitative analysis of phenolic compounds and antioxidant activity determination of the different extracts were carried out. Chemical species such as catechin, malvidin, quercetin, caffeic acid, and ellagic acid were the dominant components, found in the extracts studied. The A. chilensis extract showed the highest value of total phenolic compounds (TPC) and AA, followed by E. globulus, B. globosa and G. officinalis. Zetasizer, Fourier-transform infrared (FTIR), X-ray diffraction (XRD), transmission electron microscopy (TEM) and thermogravimetric analysis (TGA) data show that plant extracts with lower AA leads to a decrease in the yield of ZnO NPs and an increase in the amount of residual organic extract that remains on the particles. The latter caused an increase in the average particle size, PDI and ζ-potential as a consequence of agglomeration and particle coarsening. Our result suggest that it is possible to use the AA as an indicator of the potential reducing capacity of plant extracts. In this way it is possible to guarantee the reproducibility of the synthesis process as well as ensure the formation of ZnO NPs with desired characteristics.